Bringing Artificial Intelligence to Research Analytics: Research Highlighter-MatchMaker - Huang, Tianning; Li, Yuemin (Journal of Knowledge Management Practice, 2024)
It is more significant to identify accurate grant opportunities given the increasing challenges in securing grants these days. Combining Artificial Intelligence (AI) and Natural Language Processing (NLP) techniques, we have developed Research Highlighter-MatchMaker to facilitate the grant application process. The tool aims to provide an overview of research strength and to recommend matched funding opportunities as well as potential collaborators for researchers based on their research track records. It has the potential to expand to provide matching for on-campus researchers and industrial partners. It will also include a chatbot to facilitate the research administration infrastructure and process on campus.
Keywords: knowledge management; artificial intelligence; natural language processing; recommendation system; research enterprise; grant application